Pengaruh Current Ratio, Debt to Asset Ratio, dan Ukuran Perusahaan terhadap Kinerja Keuangan pada Perusahaan Makanan dan Minuman Periode 2020-2024 - Steven Wijaya; Muhammad Jusman Syah (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
This study aims to analyze the influence of company characteristics, including Current Ratio, Debt to Asset Ratio, and Company Size, on Financial Performance. The population studied consists of companies in the F& B sector listed on the IDX during the period 2020-2024. The sample in this study was selected using the purposive sampling method. Out of the 24 companies listed in the sector, 3 companies were eliminated because they did not meet the established criteria, resulting in a final sample size of 21 companies. To test the influence of independent variables on the dependent variable, the multiple linear regression analysis technique was applied. The research results show that Company Size has a positive and significant effect on financial performance, while the Debt to Asset Ratio has a negative and significant effect on financial performance. On the other hand, the Current Ratio does not show a significant effect on financial performance. However, the Current Ratio does not appear to significantly affect financial performance. While it is a measure of liquidity, the results of this study suggest that liquidity alone does not guarantee profitability or financial success. It is possible that other factors, such as market conditions or management practices, may play a more dominant role in influencing financial performance. Overall, this research emphasizes the need for companies in the F&B sector to carefully manage their debt levels and consider the benefits of growing their company size to improve financial performance. Future studies could explore the role of other factors, such as operational efficiency and market conditions, to gain a more comprehensive understanding of what drives financial success in the industry.